Development of E-Modules to Improve Scientific Explanation Skills in Science Learning for Junior High School Students - Mardhiyyah, Lailatul; Supeno, Supeno; Ridlo, Zainur Rasyid (Jurnal Pendidikan MIPA, 2022)
Scientific explanation skill is one of the essential skills for students in science learning today. Scientific explanation is a reasoning skill that relates claims, evidence, and reasoning. Students can understand, articulate, and explain scientific phenomena accompanied by evidence and reasoning with scientific explanation skills. However, in reality, students are still lacking in scientific explanation skills. In an effort to improve scientific explanation skills, teaching material is needed to be developed in the form of e-modules. The use of e-modules in learning is expected to train students' thinking skills, one of which is scientific explanation skills. This study aims to determine the validity, practicality, and effectiveness of e-modules to improve the scientific explanation skills of junior high school students in science learning. The development of the e-module is carried out in three stages, namely preliminary research, prototyping stage, and assessment phase. The results showed that e-modules were included in the valid, practical, and effective categories. Thus, the e-module can be used and applied to develop science learning outcomes and scientific explanation skills.Keywords: scientific explanation skill, e-module, science learning.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp34-44